Using organic phosphorus to sustain pasture productivity: A perspective - Nash, David M.; Haygarth, Philip M.; Turner, Benjamin L.; Condron, Leo M.; McDowell, Richard W.; Richardson, Alan E.; Watkins, Mark; Heaven, Michael W. (Geoderma, 2014)
Organic phosphorus (P) in grazed pastures/grasslands could sustain production systems that historically relied on inorganic P fertiliser. Interactions between inorganic P, plants and soils have been studied extensively. However, less is known about the transformation of organic P to inorganic orthophosphate. This paper investigates what is known about organic P in pasture/grassland soils used for agriculture, as well as the research needed to utilise organic P for sustainable plant production. Organic P comprises >50% of total soil P in agricultural systems depending on location, soil type and land use. Organic P hydrolysis and release of orthophosphate by phosphatase enzymatic activity is affected by a range of factors including: (a) the chemical nature of the organic P and its ability to interact with the soil matrix; (b) microorganisms that facilitate mineralisation; (c) soil mineralogy; (d) soil water electrolytes; and (e) soil physicochemical properties. Current biogeochemical knowledge of organic P processing in soil limits our ability to develop management strategies that promote the use of organic P in plant production. Information is particularly needed on the types and sources of organic P in grassland systems and the factors affecting the activity of enzymes that mineralise organic P. Integrated approaches analysing the soil matrix, soil water and soil biology are suggested to address this knowledge gap. [Display omitted] •Organic phosphorus (P) can be>50% of soil phosphorus in grazed pastures.•Organic P in pasture/grassland soils could be better utilised for plant production.•However, further knowledge of P transformations is needed to access that P.•This knowledge could be collected by combined matrix, soil water and biology analyses.